Antimicrobial property of sodium alginate/TiO2 nanocomposite film - Fundador, Erwin Oliver V.; Villanueva, Jessa Mae A.; Fundador, Noreen Grace V.; de Cadiz, Aleyla E. (2018)
Food poisoning outbreaks are commonly caused by bacterial contamination. These incidents can be minimized by using antimicrobial films that are suitable for use as packaging material. These films can be made by immobilizing an antibacterial agent to a non-toxic polymer matrix. Titanium dioxide (TiO2), when irradiated with ultraviolet light, produces free radicals capable of killing bacteria. Sodium alginate (SA) is an edible polymer taken from brown algae. Both TiO2 and SA are approved by the U.S. Food and Drug Administration as an additive in food. Therefore, composites made from SA and TiO2 are considered safe. SA/TiO2 nanocomposite films can be activated by both fluorescent and black light lamps. As evidenced by the percent color removal of methylene blue, the photocatalytic activity appeared to be higher when exposed to black light. SA/TiO2 composite films were exposed to fluorescent and black light lamps for 5 h in the presence of Escherichia coli and Staphylococcus aureus. Under fluorescent lamps, the photocatalytic activity of the SA/TiO2 composite films was enough to at least inhibit the proliferation of both bacteria. However, exposure of the 5% SA/TiO2 composite film to black light resulted to a 0 log count for both bacteria. These results showed that SA/TiO2 composite films can therefore be used in the food industry as an antibacterial film.